Language-Specificity in the Perception of Paralinguistic Intonational Meaning - Chen, Aoju; Gussenhoven, Carlos; Rietveld, Toni (Language and speech, 2004)
This study examines the perception of paralinguistic intonational meanings deriving from Ohala's Frequency Code (Experiment 1) and Gussenhoven's Effort Code (Experiment 2) in British English and Dutch. Native speakers of British English and Dutch listened to a number of stimuli in their native language and judged each stimulus on four semantic scales deriving from these two codes: SELF-CONFIDENT versus NOT SELF-CONFIDENT, FRIENDLY versus NOT FRIENDLY (Frequency Code); SURPRISED versus NOT SURPRISED, and EMPHATIC versus NOT EMPHATIC (Effort Code). The stimuli, which were lexically equivalent across the two languages, differed in pitch contour, pitch register and pitch span in Experiment 1, and in pitch register, peak height, peak alignment and end pitch in Experiment 2. Contrary to the traditional view that the paralinguistic usage of intonation is similar across languages, it was found that British English and Dutch listeners differed considerably in the perception of “confident,” “friendly,” “emphatic,” and “surprised.” The present findings support a theory of paralinguistic meaning based on the universality of biological codes, which however acknowledges a language-specific component in the implementation of these codes.